Genetic Enteropathies Linked to Epithelial Structural Abnormalities and Enteroendocrine Deficiency: A Systematic Review. Issue 6 (June 2021) - Caralli, Morgane; Roman, Celine; Coste, Marie-Edith; Roquelaure, Bertrand; Buffat, Christophe; Bourgeois, Patrice; Badens, Catherine; Fabre, Alexandre
ABSTRACT: Objectives: Congenital diarrhea and enteropathies linked to epithelial structural abnormalities constitute 3 different rare diseases: the tufting enteropathies (TE; EPCAM and SPINT2 mutations), microvillous inclusion disease (MVID; MYO5B and STX3 mutations), and tricho-hepato-enteric syndrome (THE; TTC37 and SKIV2L mutations). Moreover, enteroendocrine deficiencies (ED; PCSK1 and NEUROG3 mutations) share common clinical characteristics with TE, THE, and MVID in that the treatment requires, in most cases, long-term parenteral nutrition. Although numerous cases have been reported in the literature, aggregated data on morbidity and mortality are missing owing to the rarity of the diseases. Methods: We performed a systematic review of all published cases and retrieved 86 articles describing 323 patients (164 boys and 135 girls). Results: The mortality rate was 20.28%, with a median age at death of 13.5 months (range 0–228 months); the mortality risk was 30.8/1000 person-year; in half of the cases, death was caused by infections. Parenteral nutrition was required in 95.4% of patients and weaning off from parenteral nutrition was achieved in 29.35% at a median age of 23 months (range 3.3–276 months). The patients with ED linked to PCSK1 were nearly all weaned at a median age of 14 months, but most of the patients became overweight. MVID patients with MYO5B mutations were most often born preterm. ED linked to NEUROG3 mutation and THE patients usually presented with intrauterine growth retardation. Conclusions: This review presents data from 323 patients with congenital diarrhea linked to EPCAM TE, SPINT2 TE, TTC37 THE, SKIV2L THE, MYO5B MVID, STX3 MVID, NEUROG3 ED, and PCSK1 ED mutations. Abstract : Supplemental Digital Content is available in the text